HUBUNGAN PENGETAHUAN, SIKAP, KEPATUHAN TERHADAP PROSEDUR, KELELAHAN, DAN PENGGUNAAN APD DENGAN KEJADIAN MINOR INJURY PADA OPERATOR PRODUKSI PERUSAHAAN PERTAMBANGAN PASIR DI KLATEN - Rahmania, Silvia; Kurniawan, Bina; Ekawati, Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The minor injury causes mining workers lost the ability to perform the work from 1 day to 21 days include the weekend and holidays. The research site is a mining company that mines and processes crushed stone and construction river sand as well as gravel. This study aimed to analyze the association between knowledge, attitude, procedures’ compliance, fatigue, the use of PPE (Personal Protective Equipment) and minor injury occurrences. This research used quantitative method using explanatory type with cross sectional approach. The number of this research’ sample was 31 respondents taken from the production operators. Self-administered questionnaire was utilized to gather information from the respondents. The result of this research indicated that attitude, procedures compliance, and fatigue were associated with minor injury occurrences. The researcher suggests the company to modify the unsafe condition into a safer workplace and to provide the adequate PPE according to the workers’ need.